2002
DOI: 10.1002/jsfa.1092
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of fishmeal replacement by shrimp head silage protein hydrolysate in Nile tilapia (Oreochromis niloticus L) diets

Abstract: This study provides information on the use of shrimp head silage protein hydrolysate (SPH) as an alternative protein source for tilapia feeding. Six diets (28% protein, 12% lipid) were prepared where ®shmeal protein was replaced at levels of 0 (control), 10, 15, 20, 25 and 30% with the hydrolysate. The diets were supplied to Nile tilapia fry (338 mg initial weight) stocked in plastic recirculating 20 l tanks (10 animals per tank), with three replicates per treatment. After an 8 week experimental period, ®sh fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 27 publications
(17 reference statements)
4
41
2
3
Order By: Relevance
“…Whereas, in the study of Leal et al (2010), Nile tilapia (Oreochromis niloticus, L.) fed shrimp protein hydrolysate supplementation at 10% and 20% of fish meal protein replacement had greater lipid content than fish fed the control diet or that with the lowest shrimp protein hydrolysate inclusion level. Plascencia-Jatomea et al (2002) also found a similar result that body crude lipid content ranging from 5.36 to 6.72% in Nile tilapia fed diets with the increase of shrimp head hydrolysate supplementation. It could be postulated that protein hydrolysate could induce fat deposition.…”
Section: Whole Body Composition Of Shrimpsupporting
confidence: 67%
“…Whereas, in the study of Leal et al (2010), Nile tilapia (Oreochromis niloticus, L.) fed shrimp protein hydrolysate supplementation at 10% and 20% of fish meal protein replacement had greater lipid content than fish fed the control diet or that with the lowest shrimp protein hydrolysate inclusion level. Plascencia-Jatomea et al (2002) also found a similar result that body crude lipid content ranging from 5.36 to 6.72% in Nile tilapia fed diets with the increase of shrimp head hydrolysate supplementation. It could be postulated that protein hydrolysate could induce fat deposition.…”
Section: Whole Body Composition Of Shrimpsupporting
confidence: 67%
“…The obtained results are relatively agreed with those obtained by Plascencia-Jatomea et al (2002) who found that, replacing FM by shrimp head silage in the Nile tilapia diets up to 20% did not significantly affected FCR or PER while the higher replacing levels (25 or 30%) significantly adversed FCR and PER of the Nile tilapia. Fagbenro et al (1994) found that, Oreochromis niloticus and Clarias gariepinus, fed on fish silage diets (50% of the total dietary protein) showed a similar (P>0.05) FCR and PER as those of the control diet.…”
Section: Feed Intakeand Feed Utilizationsupporting
confidence: 90%
“…In this respect Fagbenro and Jauncey (1995) found that, fermented fish silage did not significantly affected dry matter, protein, lipids and ash content of catfish, Clarias gariepinus bodies. On the other hand, Plascencia-Jatomea et al(2002) indicated that, all replacing levels (10, 15, 20, 25 and 30%) of FM by shrimp head silage in the Nile tilapia diets significantly affected dry matter, crude protein, ether extract and ash contents of Nile tilapia. Soltan and Tharwat (2006) showed that partial or complete replacement of FM by FBS significantly (P<0.001) decreased protein content and increased fat, whereas fish group fed on the control diet gained the lower protein and fat content.…”
Section: Proximate Analysismentioning
confidence: 93%
“…The low pH along with bacteriocin molecules produced by certain LAB prevents the growth of harmful organisms (Shirai et al 2001). Biological fish silage production offers a great potential for the conversion of an underutilized protein to a valuable hydrolyzed product (Fagbenro and Jauncey 1998;Plascencia et al 2002;Shirai and Ramírez-Ramírez 2011). Vidotti et al (2002) reported that the proteins from biological silage were more digestible than those obtained by the chemical silage due to the autolytic process catalyzed by the enzymes present in the fish waste that degraded the proteins into short peptides and free amino acids.…”
Section: Introductionmentioning
confidence: 99%